A large national study of ferritin testing in Canadian blood donors. Issue 3 (9th December 2016) - Goldman, Mindy; Uzicanin, Samra; Osmond, Lori; Scalia, Vito; O'Brien, Sheila F.
Abstract : BACKGROUND: We assessed risk groups for iron deficiency and the feasibility and efficacy of ferritin testing in a large blood center. STUDY DESIGN AND METHODS: Donors were informed of possible testing in the predonation pamphlet. Plasma ferritin was measured on retention samples (n = 12, 595) from representative clinics. Low‐ferritin donors (<25 µg/L) were sent a letter and information sheet and not called for 6 months. Ferritin testing was repeated on 25% of donors; donor return rate and frequency were monitored. RESULTS: Low‐ferritin donors represented 2.9% of first‐time and reactivated (no donation in past 12 months) male donors, 32.2% of first‐time and reactivated female donors, 41.6% of repeat male donors, and 65.1% of repeat female donors. A mean of 11.7 months after index donation, the return rate was 76% for normal and 58% for low‐ferritin donors; returning low‐ferritin donors had made approximately one fewer donation. Ferritin increased by 16.3 and 12.1 µg/L in male and female low‐ferritin donors and decreased by 17 µg/L in male and female normal‐ferritin donors. CONCLUSION: The minimum hemoglobin level will be increased to 130 g/L for male donors and the minimum interdonation interval changed to 84 days (four donations yearly) for female donors based on iron deficiency risk groups. Large‐scale ferritin testing was feasible. Donors informed of low‐ferritin results had a lower return rate, donated less often, and had an increase in ferritin on return, approximately 1 year after initial testing, compared to donors with normal ferritin results.